AC650, AC653, AC656 and AD460 antibodies label the mouse CD8α protein by immunofluorescence - Khadam-Al-Jame, Tasnim; Gillet, Hugo; Garrido, Eva; Lung Perez, Maria; Berlincourt, Jade; Zholdokov, Maxime; Ollagnon, Marin; Calomeni, Alexis; Lopez Naveira, Patricia; Tamrat, Bethania; Baltazar, Luca; Michel, Garance; et al. (Antibody Reports, 2022)
The recombinant antibodies AC650, AC653, AC656 and AD460 detect by immunofluorescence the mouse CD8α protein.